Identificación de mercados internacionales de pulpa de lulo castilla congelado - Barreto Barajas, Laura Cristina (Universidad Antonio Nariño, 2022)
Colombia is a country with diverse geography, therefore, it has a wide range of agricultural products to offer, not only in the interior of the country, but also has an export potential due to the climatic and soil conditions, which allow at all times of the year to obtain wide harvests of fruits endemic to the region. The lulo (Solanum quitoense Lam) is a shrub native to the Andes, specifically Colombia and Ecuador, produces those fruits of green pulp, which for their color, flavor and nutritional properties are desired in national and international markets, this fruit belongs to the family of Solanáceas (ICA, 2012).